Removal of hydrogen fluoride from gas streams - Rampersadh, Pradish (My University, 2006)
The removal of hydrogen fluoride (HF) from fluorine (F2) and other media, e.g. inorganic and organic compounds, is normally achieved by adsorbing HF onto sodium fluoride (NaF). The aim of this study was to assess alternative adsorbents for the removal of HF in the gas phase. It deals more specifically with the sorption of HF by inorganic compounds, ion exchange resins, and carbon based materials. Further the study can be classified as a hermogravimetric study as this was the principle analytical tool used in this investigation. This study also aims to address some of the controversy surrounding the removal of HF by calcium salts. Firstly, commercial calcium salts (viz. CaF2, Ca(OH)2, CaCl2 and CaSO4) were assessed for HF removal in the presence of fluorine. Other inorganic adsorbent were also investigated e.g. mixtures of NaF with other metal fluorides and an aluminophosphate molecular sieve. It was noted that most of the calcium salts do have a capacity for HF, but can release their anions as impurities in the gas streams. However, the other inorganic adsorbents, including CaF2 did not have an HF adsorbtion capacity. Secondly polymeric resins were assessed for HF removal in non-fluorine environments, in particular, a perfluorinated resin, a polyacrylate and a series of commercial ion exchange resins. Most of the polymeric material did have a HF capacity, however the weak base acrylic resins has the best capacity and kinetics for the removal of HF from organic streams. Finally, considering pure carbon is inert with reference to HF, three types of carbon-based structures were investigated for HF uptake, viz activated carbon, carbon molecular sieves and nanotubes. From the results obtained, most forms of carbon do have a capacity for HF. These including impregnated activated carbons.
Faculty of Science, School of Chemistry, PhD Thesis